Comparison of RADEC Learning Model and SQ3R Learning Model on Reading Interest of Elementary School Students - Sulfasyah, Sulfasyah; Adriana, Adriana; Rukli, Rukli (Jurnal Pendidikan MIPA, 2022)
Students’ interest in reading is increasingly demanded according to the challenges of the 21st century. However, students’ interest in reading decreases when technology develops, where the flow of data and information is getting faster and more complex. Therefore, there needs to be a learning model in the classroom to increase students’ reading interest. The study examines the RADEC learning model with the SQ3R learning model on students’ reading interests. This type of research is quantitative with quasi-experimental research. The research design used was a pre-test, post-test non-equivalent multiple group design. The population of this research is fifth-grade students in Tanete Rilau Subdistrict, Barru Regency, South Sulawesi. Sampling was done randomly. The results showed that the average reading interest of students in the RADEC learning model was higher than in the SQ3R learning model. There is a significant difference between the RADEC learning model and the SQ3R learning model on interest in reading for fifth-grade elementary school. Therefore, teachers can use the RADEC learning model to increase students’ reading interest in schools. Keywords: RADEC learning model, SQ3R learning model, reading interest. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp968-978